From Definition to Need: Redefining the Selected Topics in Mathematics Education Course Through Students’ Mastery Profiles - Santri Chintia Purba; Candra Ditasona; Stevi Natalia (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
This study aims to analyze mathematics education students’ mastery of high school mathematical content and their readiness to teach it, as a basis for redefining the design of the Selected Topics in Mathematics Education (Kapita Selekta) course. A quantitative descriptive survey design was employed involving 14 mathematics education students at Universitas Kristen Indonesia who were enrolled in the Kapita Selekta II course. Data were collected using a questionnaire that assessed students’ mastery and willingness to learn and teach 32 high school mathematics topics. Descriptive statistics were used to determine the percentage of mastery and non-mastery for each topic. The findings reveal that only 40.13% of topics were mastered, while 59.87% showed a lack of mastery. Students demonstrated stronger understanding in algebraic and symbolic topics such as sequences, exponents, relations, and matrices, but weaker performance in geometry, trigonometry, and calculus-related topics. Despite these gaps, all respondents expressed a willingness to improve their mastery of mathematical content, with 42.9% being very willing and 57.1% willing to do so. These results suggest that the Kapita Selekta course should not be limited to topic selection based on theoretical definitions. Instead, it should be redesigned to respond to students’ actual mastery profiles and learning needs. By aligning course content with diagnostic data, the program can strengthen students’ mathematical competence and pedagogical readiness to teach effectively at the high school level.